Pengalaman Komunikasi Perempuan Korban Kekerasan dalam Pacaran - Alya Difa Salsabila; Atwar Bajari; Agus Setiaman (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Dating violence is a phenomenon that is rife in society. Basically, or dating violence is a problem that continues to get an increase in every case, especially in women's gender-based violence. This study aims to determine the motives of women to endure dating violence, patterns and forms of violent behavior experienced by women while involved in dating relationships, and the meaning of actions and also violent relationships based on the experiences of each informant. This study uses a qualitative phenomenological approach with symbolic interaction theory, phenomenological theory, and social construction theory. The research results were obtained through structured and semi-structured in-depth interviews with five female informants who experienced this phenomenon. The results of the study show that women's motives for surviving violence in their relationship can be seen from two different motives, namely past motives due to affection and an imbalance of positions in relationships that make women powerless. On the other hand, the past motive that underlies women to survive is because they feel their partners are very good outside of the violence. Meanwhile, when viewed from the future motive, it is because the woman still believes that her partner can change for the better for herself and also for the relationship. Regarding the experience of communication in the form of violence experienced by the informants, there was verbal and physical violence. Patterns of violence can occur because of various conflicts, such as the woman's feeling that she has violated the rules of her partner, feelings of jealousy, her partner's prejudice, and her partner's stubbornness about what he thinks is right, which makes the partner emotional and ends up committing violence. Of course regret and false promises are mentioned by the partner which makes the woman accept and forgive her behavior again. Meanwhile, from the length of their relationship, the women interpret or view the phenomenon of dating violence as an act that is wrong. So they interpret the relationship as not to be fought for and feel that an abusive relationship can cause trauma. On the other hand, there are also other opinions that being involved in a violent relationship gives insight on how to deal with someone with unstable emotions, so that it can be used as a learning relationship in the future.